New phases of 3d-transition metal–cerium binary compounds: an extensive structural search. Issue 64 (21st August 2017) - Sun, Xiaorui; Lei, Yawei; Zhou, Rulong; Qu, Bingyan; Li, Dongdong; Zhang, Bo; Zeng, Xiao Cheng
Abstract : The phase stabilities, structural features, electronic and mechanical properties of 3d transitional metal–cerium binary compounds were systematically studied. Abstract : We perform a comprehensive study to explore the low-energy crystalline phases of 3d transitional metal–cerium (TM–Ce) binary compounds using an unbiased structural search method coupled with first-principles optimization. For Ce–Sc, Ce–Ti, Ce–V, Ce–Cr and Ce–Mn binary systems, no stable crystalline phases are found from the structural search, offering an explanation for why none of these binary compounds have been observed in experiments. For Ce–Fe, Ce–Co, Ce–Ni, Ce–Cu and Ce–Zn binary systems, in addition to the previously known experimental structures, we also find several new low-energy crystalline phases. The computed electronic structures show that Ce atoms are in different states in the predicted binary compounds. In the Ce–Fe, Ce–Co and Ce–Ni compounds, the Ce 4f electrons are partially itinerant so that Ce atoms tend to adopt intermediate valence states between Ce +4 and Ce +3 due to the hybridization among Ce-4f, Ce-5d states and 3d states of TM. In the Ce–Cu and Ce–Zn binary compounds, the Ce-4f states are more localized with the charge state of Ce being close to 3+. In particular, the ferromagnetic metal (FM)-rich phases of the Ce–Fe, Ce–Co and Ce–Ni compounds tend to exhibit FM ordering in their ground states, owing to the strong exchange interaction among metal elements, whereas the non-magnetic states are usually preferred for FM-deficient phases. Magnetic orderings are also found in some other TM-rich phases of Ce–Cu and Ce–Zn compounds, where the magnetic moments are located on the Ce atoms due to the Kondo effect. Mechanic properties of these compounds are also computed based on density functional theory methods. This systematic study offers significantly new data for Ce-based alloys and will be useful to understand the intriguing behavior of the Ce-4f electron, thereby calling for future experimental confirmation of the newly predicted phases of Ce–TM compounds.